The Effect of Work-Life Balance and Work Engagement on Turnover Intention at The Tirta Sanjiwani Regional Public Water Utility (PDAM) in Gianyar Regency - Wiracahyani, Made Febri; Astiti, Ni Putu Yeni; Adhika, I Nyoman Resa (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Every organization naturally wants to have high-quality human resources (HR). The role of HR extends beyond administrative tasks such as recruitment and employee administration; it also encompasses the development, retention, and management of human potential within the organization. The large number of employees in an organization undoubtedly requires effective management to ensure they remain a cohesive unit. However, it cannot be denied that in today’s era, human nature—which is inherently self-centered, seeks personal security, and strives for the best for oneself—leads to the phenomenon of turnover intention. The purpose of this study is to examine the influence of work-life balance and work engagement on turnover intention, as well as the influence of work engagement on work-life balance. The sample in this study consisted of 56 non-permanent employees at the Regional Public Water Supply Company (PDAM) Tirta Sanjiwani in Gianyar Regency. The research sample was selected using a saturated sampling method. The data analysis technique employed was regression analysis. The results of the study indicate that work-life balance has a negative and significant effect on turnover intention, work-life balance has a positive and significant effect on work engagement, and work engagement has a negative and significant effect on turnover intention.